Los beneficios premiales que pueden obtener las personas jurídicas que celebren acuerdos de colaboración eficaz en el marco de la Ley 30737 y su Reglamento - Calderón Jacinto, Liliana (2018)
Throughout this article, the premial benefits that may be generated by Law 30737 and its regulations are developed, achieving to exclude legal persons from the scope of application thereof. This Law seeks to ensure the payment of civil compensation in favor of the Peruvian State, by those guilty parties in cases of crimes against public administration, corruption, among others. In addition, the concept of the effective collaboration procedure within our national legislation is highlighted, describing it as one of the modern premial mechanisms that are introduced to face organized crime in Perú.